Evaluation of Radiation Workers Occupational Doses for Newly Established Medical Center NORIN Nawabshah in Pakistan - Abdul Razaq; Muhammad Waqar; Quratulain Soomro; Muhammad Ali Javaid (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2016)
AbstractThe purpose of this study is the evaluation of radiation doses received by radiation personnel in newly established medical Centre, Nuclear Medicine Oncology and Radiotherapy Institute Nawabshah (NORIN) Pakistan. In this study the annual dose data of workers for the year 2013 and 2014 in different sections will be analyzed using different statistical methods and results. It will be discussed that how we careful in occupational radiation dose and comparison with national and international organization will be done to know that the facility in NORIN for radiation protection is reasonable and satisfactory.